Pengaruh Kepemimpinan Transformasional Dan Pelatihan & Pengembangan Terhadap Kinerja Pegawai Puskesmas Melalui Motivasi Kerja - Kartikawati, Era; Sutarso, Yudi; Setia , Shinta (Jurnal Ilmiah Administrasi Publik, 2026)
This study aims to analyze the influence of transformational leadership style and training & development on employee performance through work motivation among Puskesmas employees in Surabaya. The research employed a quantitative approach using Structural Equation Modeling (SEM) PLS with a sample of 135 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that transformational leadership (β = 0.360; t = 4.163) and training & development (β = 0.301; t = 4.065) had a significant positive effect on employee performance. Both also positively influenced work motivation, with coefficients of β = 0.533; t = 8.149 and β = 0.415; t = 5.937, respectively. Furthermore, work motivation significantly affected employee performance (β = 0.313; t = 2.889) and significantly mediated the relationship between transformational leadership (β = 0.167; t = 2.617) and training & development (β = 0.130; t = 2.587) with employee performance.